ANALISIS KUALITAS AIR DAN BEBAN PENCEMARAN AIR PADA SUB DAS BOENTUKA KABUPATEN TIMOR TENGAH SELATAN - Umbu A Hamakonda; Bambang Suharto; Liliya Dewi Susanawati (Universitas Andalas, 2019)
Rivers in the Boentuka Sub-watershed of Timor Tengah Selatan Regency have been shown to experience pollution caused by domestic and agricultural activities. This study aims to assess water quality and identify river water pollution loads based on water quality according to Government Regulation Number 82 of 2001 concerning water pollution management and control. The parameters analyzed were physical, chemical, and biological, the length of the river in the Boentuka Sub-watershed was 15km. The method of river water pollution index from upstream to downstream in 6 sampling points with test parameters such as the biological oxygen demand, chemical oxygen demand, fecal coliform and total coliform in the downstream has exceeded the criteria of class I water quality standards according to PP No. 82 of 2001. Pollution index of 1.11 to 4.62. This shows that the quality of river water has been polluted with mild pollution status. While the pollution load of domestic waste dumped into the river is on the biological oxygen demand parameter of 6297,584 kg / day and chemical oxygen demand of 7871.98 kg / day, fecal coliform pollution load of 458.0108 MPN / day and totalcoli 1210.121 MPN / day